Improving the Quality of Mathematics Learning in Elementary Schools through Lesson Study Using a Scientific Approach - Asri, Rian Puji; Suryadi, Didi; Al Jupri (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2022)
The quality of learning in the classroom is inseparable from the ability of a teacher to implement his knowledge in the learning process. Various strategies, methods, and approaches have been carried out to improve the quality of learning. One of the efforts made by the government is to change the learning approach that was originally teacher-centered to student-centered, the approach in question is scientific. This study tries to explore the implementation of lesson study using a scientific approach to improve the quality of mathematics learning in elementary schools. This research was conducted in an elementary school in Purwakarta. Based on the results of the study it was found that lesson study is an effective way to improve the quality of mathematics learning in elementary schools. the use of a scientific approach also has an impact on learning activities with five stages of scientific thinking, namely observing, asking, trying, reasoning, and communicating to stimulate students to be active and think critically.